Conservation strategies for contemporary street art in Pretoria : a study of Jared Pereira’s public paintings - Loubser, Maggi (University of Pretoria, 2023)
Mini Dissertation (MSocSci (Tangible Heritage Conservation))--University of Pretoria, 2022.